Assessment and Control of Rock Massifs State for Sustainability of Natural and Man-Caused Slopes and Underground Structures under Influence of Contemporary Seismic and Tectonic Processes - A. D. Melikulov; K. D. Salyamova; N. Yu Gasanova; A. S. Ismailov (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 8, 2023)
The article discusses issues pertaining to the unique formation and temporal changes in the stress-strain state of rock massifs as objects of active human impact from engineering facilities, both surface and subsurface, hydrotechnical and road construction, mining operations, including the development of mineral deposits by open-cut and underground methods. Arrays of rock formations have a wide range of properties that manifest themselves as hazardous natural geological events, and also under any technological influences to them, including the method of blasting destruction. The peculiarities of the behavior of such arrays consist in the combination of the characteristics of solid as elastic and plastic bodies, including brittle, and viscous-flowing bodies, and creep. In terms of the object’s stability and safety as well as the necessity for additional material expenses to maintain the equilibrium in the new conditions, technological impact on the rock mass might have unintended and dangerous implications. The identification of the potential area of permissible deformations and the conditions for the destruction of such an array of rocks, taking into account the time factor, is of practical interest for selecting effective parameters of mining technology that allow the prevention of dangerous undesirable consequences of destruction. In areas where physical experiments in the traditional view are challenging, such as in underground mining facilities, processes of destruction, and mining of minerals using blasting technologies, numerical methods of modelling mining-geological objects and processes of any complexity with the use of modern technical and software tools offer new opportunities in solving technological problems.